Diagnosis and Management of Interventional Endovascular Carotid-cavernous Fistula: a Retrospective Study - Luh Putu Lina Kamelia (Journal of Global Pharma Technology, 2020)
Carotid-cavernous fistula (CCF) is a consequence of incremental intracavernous pressure. The direction of drainage is usually multidirectional. Initial DSA (digital subtraction angiography) solves in obtaining its information along with advanced technology nowadays. Aim: The study aims to analyze clinical characteristics, cerebral angiographic features, and management of endovascular embolization of CCF. Methods: The study is a retrospective analysis of each patient diagnosed with CCF. They were treated with endovascular embolization from January 2019 to April 2010 at the Brain Center Dr. Wahidin Sudirohusodo (DWS) General Hospital Makassar. We performed DSA on all patients before the endovascular procedure with catheterized access through the right femoral artery. Result: Angiograms of all patients showed typical CCF lesions, 8 patients then received endovascular management by coiling method, 2 were treated with a detachable balloon, while 1 received an Onyx injection. All patients experienced gradual improvement for orbital symptoms. Conclusion: Endovascular embolization-followed cerebral DSA is a useful diagnostic and therapeutic management to improve patients' clinical symptoms with CCF. Keywords: Carotid-cavernous fistula, Digital subtraction angiography, Embolization, Balloon, Onyx.